2000
DOI: 10.1054/bjoc.1999.0973
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 production in ovarian carcinoma is associated with histiotype and biological characteristics of the tumour and influences local immunity

Abstract: The presence of interleukin (IL)-6 in peritoneal carcinomatous fluid (PCF) and its effect on immune cells composition in PCF in patients with advanced ovarian carcinoma was studied. In 21 out of 30 ovarian carcinoma patients, PCF IL-6 levels were found to exceed those seen in PCFs of patients with gastrointestinal cancer. IL-6 activity was higher in serous/mucinous than in endometrioid and undifferentiated ovarian carcinoma PCF (P = 0.05). Ovarian carcinoma PCF IL-6 activities were correlated with serum C-reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 24 publications
2
25
0
1
Order By: Relevance
“…High interleukin-6 (IL-6) levels in the ascitic fluid of ovarian cancer patients were correlated with poor prognosis (6). Other studies have highlighted the crucial role of IL-6 in the pathogenesis of ovarian cancer (54,55). In the present study, we found significantly higher levels of macrophage chemoattractant protein-1 (MCP-1; >2.5-fold) in SP À/À ascitic fluid (Fig.…”
Section: Sparc Ameliorates the Peritoneal Tumor -Induced Inflammationsupporting
confidence: 64%
“…High interleukin-6 (IL-6) levels in the ascitic fluid of ovarian cancer patients were correlated with poor prognosis (6). Other studies have highlighted the crucial role of IL-6 in the pathogenesis of ovarian cancer (54,55). In the present study, we found significantly higher levels of macrophage chemoattractant protein-1 (MCP-1; >2.5-fold) in SP À/À ascitic fluid (Fig.…”
Section: Sparc Ameliorates the Peritoneal Tumor -Induced Inflammationsupporting
confidence: 64%
“…Other cytokines that may have a significant effect on the composition of the tumour-infiltrating lymphocyte pool are TGFb and IL-6, which have both been found in abundance in a variety of tumours, particularly advanced tumours (Asselin-Paturel et al, 1998;Conrad et al, 1999;Kryczek et al, 2000). IL-6 recently emerged as a major player governing the differentiation of naive T cells.…”
Section: Inducible Tregsmentioning
confidence: 99%
“…EOC cells in vitro have also been demonstrated to modulate the macrophage phenotype by inducing the expression of inflammatory mediators (Hagemann et al, 2005). Among the cyto/ chemokines found in EOC ascites, IL-6 has been shown to be a growth-promoting and anti-apoptotic factor (Kryczek et al, 2000). Moreover, patients with high levels of IL-6 expression have shorter survival than patients with lower levels (Penson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%